Realitas persekusi pada kalangan masyarakat sekolah di Kabupaten Pangkep Sulawesi Selatan - Ibrahim Ibrahim; Muhammad Said; Hasni Hasni (Seminar Nasional LP2M UNM, 2019)
The title of this research is Persecution Realty on school community in Pangkep Regency, South Sulawesi). The purpose of this study is: To analyze the reality of persecution in the school community. The nature of the research is qualitative with a phenomenological approach. The data collection techniques are: interview, observation, documentation. The data analysis of this research was categorized. Research results show that in school communities also often experience anomalies in achieving the noble goals of school. the number of cases of threats, bullying, harassment, torture, violence, abuse, oppression, discrimination experienced by a particular person or group in the school shows the reality that the behavior of persecution is evident in the school community even though the intensity and polarization are different different.